Rhetorical Anomalies and Resistance to the Standard of Handsomeness in MS Glow Men Advertisement - Diyana Elissa; Rustono Farady Marta; Maichel Chinmi; Engliana Engliana; Azizah Nur Aulia (Universitas Multimedia Nusantara, 2026)
Media distort people's perceptions of reality and force them to display the standard of good looks is the foundation for the development of standards of good looks in men. This research aims to find out how the MS Glow for men ad version of Marshel Widianto X Babe Cabiita breaks the stigma of good looks standards in society and the media. Using the dramatism theory and Kenneth Burke's pentad analysis method. The results of this study indicate that the pentad element of attitude is a prominent element in the actions displayed in the MS Glow for Men advertisement version of Marshel Widianto and Babe Cabiita. This is the difference in attitude displayed between the front screen and the back screen of the main character's daily life, so it can be said that handsome is not only from a physical appearance but also from within, namely person's behavior and character are indicative of their moral standing. in society. In addition, the pentad element of agents and scenes is a prominent and influential element. Featuring non-model actors in facial care product advertisements and a comedian break the standard of handsomeness that already exists in society and the media.